2011
DOI: 10.1590/s0103-507x2011000200014
|View full text |Cite
|
Sign up to set email alerts
|

Sepse: atualidades e perspectivas

Abstract: This paper aims to provide an update on the main aspects of sepsis, a very relevant health care issue. A number of hypotheses have been proposed to explain its origin, involving interactions between microorganisms and the innate immune system, inflammation/immune mediation and the coagulation system. The clinical features of sepsis are variable and depend on the primary site of infection. The identification of early signs and symptoms is crucial for starting therapeutic measures fundamentally based on volume r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 41 publications
(44 reference statements)
1
24
0
8
Order By: Relevance
“…and Enterobacter spp., were isolated most frequently. (3,6,12,(27)(28)(29) An American study assessing only late-premature children has demonstrated that S. aureus and E. coli are often present in blood cultures. (7) The cross-sectional and retrospective nature of this study is a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…and Enterobacter spp., were isolated most frequently. (3,6,12,(27)(28)(29) An American study assessing only late-premature children has demonstrated that S. aureus and E. coli are often present in blood cultures. (7) The cross-sectional and retrospective nature of this study is a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Sepsis is defined as a Systemic Inflammatory Response Syndrome (SIRS) triggered by a suspected or confirmed infection that can develop into severe sepsis when associated with organ dysfunction or septic shock (1)(2) . This disease is a public health problem and a challenge for healthcare organizations because it is among the leading death causes in hospitalized patients (3) .…”
Section: Introductionmentioning
confidence: 99%
“…O desenvolvimento da sepse depende das relações estabelecidas entre o microrganismo e o hospedeiro destacando-se que, muitos dos elementos relativos ao seu aparecimento permanecem obscuros, provavelmente pela falta de uma compreensão mais adequada no que se refere à imunidade, inflamação e coagulação. 3,4,5,6 Os pacientes sépticos exigem maior tempo de internação na UTI, resultando num maior custo de tratamento comparado a outros pacientes. Nos EUA, a sepse é a 10ª causa de morte, sendo apontado por um estudo de fármaco-economia europeu um gasto direto de 23.000 a 34.000 euros.…”
Section: Introductionunclassified